Releituras teóricas e metodológicas da lógica tradicional aristotélica na prática de classificação da BCI: um exemplo de conversão de um modelo epistemológico para um modelo ontológico, aplicado na classe agricultura da CDU - Tereza Cristina Fernandes Pontes (2020)
Classification is one of the main processes for organizing and representing the knowledge used by Librarianship and Information Science (BIS). In the Universal Decimal Classification (UDC), the procedure used is an instrumentalization of the classification of sciences with an epistemological approach. However, researchers consider this approach to be inappropriate for classification practices, but consider it opportune bringing BCI and Philosophy closer together. In this regard, this research explores an alternative to epistemological classification, encompassing realistic ontological procedures by the philosopher Aristotle within the scope of the Categories treatise. Simultaneously, it seeks answers to the dissertation on: i) problems immanent to the prescriptive classification; ii) inquiries about the type of object and the type of classification of the CDU, analyzed from the perspective of the procedure and criteria of Aristotelian logic. The main objective of this research is to formalize the logical classification present in the Categories treaty by applying its realistic procedures to samples of the agriculture class of the CDU. To achieve this goal, the methodology is characterized as exploratory, qualitative and descriptive. Applies in the Bibliographic Research techniques of critical reading of philosophical texts used in Philosophy research plus techniques of categorization of content analysis, with the purpose of extracting the key operators from the Categories treaty, useful for the formalization of an executable classification artifact at BCI. For the formalization of an existing artifact of the Design Proposition type, the CIMO logic technique was used in the Design Science methodology. To achieve the specific objectives and assumptions proposed in the research, four steps are taken from the elaboration of the following proposition: If the classification of the CDU is subjective and implicit (class of contexts), use theories of Aristotle's realistic approach (type of intervention) to create a logical classification (intended result) through the application of procedures and criteria of the Categories treaty (generative mechanisms). Each step resulted in a result: 1) the objects in the UCD sampling are universal accidental; 2) the classification of the UDC is enumerative; 3) realistic procedures investigate the thing-in-itself, reducing subjectivity in the classification; 4) the application of key operators, procedures and criteria of the Categories treaty outline the objects of the UDC with logical chain in the classification. Finally, it is emphasized that the practices and theories of the Aristotelian realistic ontological system come from rigorous justifications and criteria that can give a more adequate basis to the classification practices in Library and Information Science.